Taghayyur al-Mustawā al-ām lil- Athār wa Arahu ala al-ḥuqūq wa al-Wājibāt - Nuruddin Nuruddin (Al-Jami'ah: Journal of Islamic Studies, 2002)
The hardest economic problem faced by human being is the instability or the fluctuation of prices. This phenomenon is closely related to inflation, i.e., the uprising of prices continuously, or the decrease of the value of a currency toward goods and services. As an example, someone borrowed to someone else as much as 1 million rupiahs and returned it back two years later with the same amount. Due to the inflation during that period, the value of 1 million rupiahs in the time of transaction is very different from that in the time of return. This problem has been becoming one of the polemics among fuqaha, either in the medieval era or in the modern one. This article is trying to observe the problem more objective without relying on a certain school of Islamic jurisprudence (madhhab), and providing the best ijtihad derived from certain fuqaha. Some considerations to decide which would be the best ijtihad are the arguments on which the fuqaha’s based on their decision. Besides, the writer also takes into account some norms of Islamic jurisprudence: taysir (to take it easily) and 'adamul haraj (to exclude obstacles). Finally, the writer offers some discussion on the issue among contemporary fuqaha.